Marital and family relationships among women with severe mental illness during perinatal period admitted to a mother baby psychiatric unit, India - Kaur, Gurinder Preet; Vaiphei, Kimneihat; Ganjekar, Sundernag; Thippeswamy, Harish; Chandra, Prabha S.; Desai, Geetha (International Journal Of Community Medicine And Public Health, 2023)
Background: Pregnancy and transition to parenthood is often a stressful event and brings about more profound changes than any other developmental stage of the family life cycle. Consequently, pregnancy and post-partum are times of increased vulnerability for the onset or relapse of a mental illness. The current paper aimed at understanding the marital and family relationships among women with severe mental illness during the perinatal period in India. Methods: The study included a retrospective chart review of mothers admitted to a mother-baby unit between the years January 2015 to March 2020. We included all mothers who were married and had onset of SMI in the perinatal period. Details of socio-demographic, clinical profile and descriptive understanding of relationships were collected. Results: The total sample was 149, mean age of women in years was 25.27 (SD=4.97). The clinical diagnosis included non-affective psychosis (45.5%), affective psychosis (42.2%) with 130 (87.24%) women having their first episode of SMI during the postpartum period. More than half of the women admitted to the ward reported having problems in their marital relationship, with 25% experiencing violence from their spouses and in-laws. Interpersonal issues with their in-laws in the context of violence, household chores and poor support. Conclusions: This study highlights the importance of routine assessments of the quality of marital and family relationships including domestic violence. There is a need to provide interventions aimed at helping women deal with difficulties in intimate and social relationships.